Best $n$-Term Approximations with Restrictions - Stepanets, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We determine exact values of the best $n$-term approximations with restrictions on polynomials used for the approximation of $λ, q$-ellipsoids in the spaces $S^{p,\, μ}_{φ}$.